Relationship between employee competency, work climate and work efficiency among registrars at Malaysia land offices - Mohd Ibramsah, Mazrina; Idris, Khairuddin; Uli, Jegak; Omar, Zoharah (2011)
Since globalization has become the major human resource challenge, public sector as well as private sector has to improve their service delivery through human resources ability and capabilities. Efficient public service workforce will help to ensure business success, continuous economic development and Malaysia’s competitiveness. Holman & Snee (2000) believe that to increase human work efficiency, the integration of these elements (knowledge and skill to do the work, motivation, positive work area and less hassle in the work process) is required. In order to design a workable and precise training program for human resources efficiency issues, it is imperative for related agencies to measure work efficiency and identify the extent to which competencies and work climate influence work efficiency. Therefore, this study will be conducted to determine the significant contribution of competency level of employees (Managerial leadership skill, communication skill, knowledge on job related, Self-concept (self-confident), work experiences and motives) and work climate (structure, standard, responsibility, recognition, support and commitment) towards work efficiency among registrars at Malaysia land offices.